Artificial intelligence and the dawn of an algorithmic divide - Eder, Maximilian; Sjøvaag, Helle (Frontiers in Communication, 2024)
Emerging technologies like artificial intelligence (AI) and algorithms reshape news curation and consumption. Against this background, previous research has been focused on divides between groups regarding access to such digital technologies. However, disparities in awareness and knowledge of AI across socio-demographic groups persist, potentially leading to an algorithmic divide. Despite this situation, there is still limited research into such an emerging inequality. Building on the framework of algorithmic literacy, this study aims to contribute to this gap with findings from a national representative study in Germany (N=1,090) in January 2022, considering sociodemographic factors such as age, gender, and education. Findings shed important light on the extent to which news audiences are knowledgeable about the use of AI and algorithms in news selection and recommendation, as well as in society. The results of our analysis imply that newsrooms should increase their knowledge about the potential divides created by applying AI across sectors to various socio-demographic groups and stay vigilant about the level of transparency of their AI use.